Antarctic Ascidians (Tunicata) of the French-Australian survey CEAMARC in Terre Adélie - Monniot, Françoise; Dettai, Agnès; Eleaume, Marc; Cruaud, Corinne; Ameziane, Nadia (Zootaxa, 2011)
A large collection of ascidians was made during the CEAMARC Aurora Australis V3 cruise off Terre Adélie and George V Land a region rarely investigated before at these depths. Sampling was performed by beam trawls and a dredge between 138°– 146° latitude East and from 150 to 1700 m depth, on the Antarctic shelf and slope. Three of the 33 ascidian species identified are new and belong to the Stolidobranchia. Half of the species have an exclusive Antarctic distribution, others also occur in Sub-Antarctic areas, but none are common with the southern temperate fauna. The CEAMARC collection does not contain the whole range of already known species from this region. Moreover, brittle and very small specimens were not collected. COI sequences were obtained for 37 specimens, including two of the new species.